Inclusive Islamic Politics: The Debate of Islam and Pancasila Among the Academic Communities of Islamic Religious Colleges - Khamami Zada (UIN Syarif Hidayatullah Jakarta, 2022)
Since the beginning of independence, Pancasila as the state ideology has been becoming a debate along with the increasing Islamic political awareness among Muslims. This study aims to analyze the debate among college students, lecturers and directors of the Islamic Religious Colleges (STAIs) about Pancasila as the state ideology. It used a quantitative research method with a total sample of 222 students at semester 5 disproportionately allocated to each selected college. The sampling in this survey was conducted by means of Stratified Multistage Sampling with the confidence level of 95%. This research was also strengthened by qualitative data that were extracted by interviewing the directors and lecturers of Islamic Religious Colleges (STAI) in Semarang, Denpasar, Jambi, Kupang and Banjarbaru. From this research, it can be concluded that the college students, lecturers and directors of STAIN have supported Pancasila as the state ideology that is not contradicting to Islam and will defend Pancasila as the state ideology. They also do not expect Pancasila to be replaced with Islam. This tendency then has shown the face of inclusive and moderate Islamic politics among college students, lecturers and directors of STAI. Keyword: Islamic Politics, Pancasila, Academic Communities.